Keberadaan Escherichia coli Pada Air Sungai Musi Kota Palembang - Masito, Masito; Novianti, Dewi; Marmaini, Marmaini (Indobiosains, 2024)
This research is entitled The Existence of Escherichia coli in Musi River Water, Palembang City. This research was conducted from April to May 2024 at the Palembang Public Health Laboratory Center. This research aims to analyze the number of E.coli in the Musi River water in the city of Palembang. The location for sampling river water is divided into 3 (three) stations, namely upstream (Musi VI), middle (Ampera) and downstream (Musi IV).  Each river water sample was taken 2 (two) times on different days at low tide. This sample was taken by purposive sampling and 10 ml of each river water sample was taken. River water samples were tested using the membrane filter method. The results showed that the ALT value in river water at station 1 on the 1st day was 2.2 x 103 CFU/ml, at station 1 on the 2nd day as much as 2.4 x 103 CFU/ml, at station 2 on the 1st day as much as 1.9 x 103 CFU/ml, at station 2 on the 2nd day as much as 2.3 x 103 CFU/ml, at station 3 on the 1st day as much as 1.7 x 103 CFU/ml, at station 3 on the 3rd day as much as 2.1 x 103 CFU/ml. All positive samples contained E.coli bacteria, and exceeded the threshold for hygienic water and sanitation, namely above 0 CFU/100 ml (Permenkes, 2023)